Erratum to “Emergency department based intervention with adolescent substance users: 10 year economic and health outcomes” [Drug Alcohol Depend. 165 (2016) 168–174] ((2016) 165 (168–174)(S037687161630151X)(10.1016/j.drugalcdep.2016.06.005)) - Tait, Robert; Teoh, L.; Kelty, E.; Geelhoed, E.; Mountain, D.; Hulse, G. (Elsevier Ireland Ltd, 2016)
The publisher regrets that the wrong image was used for Fig. 1 a and b. The correct figure is reproduced below for reference. The publisher would like to apologise for any inconvenience caused.